(untitled) (Journal of Business and Technology (Dhaka), 2015)
This study is an attempt to identify the factors which affect consumers in purchasing toiletries products in Khulna City, Bangladesh. Data were collected from Consumers of the city using structured questionnaire. More or less a random sampling method was applied to collect response from 250 consumers from which 197 found free from errors; those respondents were used for the ultimate study. Factor analysis and ANOVA with SPSS were applied for data analysis. This study has found that the factors consumers consider for their purchasing decisions are brand image, cost and commitments, distinctiveness, prestige, customer relationship. Except distinctiveness, individuals with various education levels do not show different perceptions on these identified factors. DOI: http://dx.doi.org/10.3329/jbt.v9i1.22779 Journal of Business and Technology (Dhaka) Vol.9(1) 2014; 71-81